ANALISIS YURIDIS PENGENAAN PAJAK PERTAMBAHAN NILAI (PPN) DALAM PEMBIAYAAN MURABAHAH DI PERBANKAN SYARIAH - AH. Azharuddin Lathif (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
The requirement of the Value Added Tax (PPN/ Pajak Pertambahan Nilai) on the murabahah endowment at the Islamic banking has created legal problems and led to the Islamic banking insolvency or ruin. Such ruin will mainly results from the fact that the murabahah product at the Islamic banking is not compatible with the credit applied in the conventional banking that is freed from the PPN. This is ironic as the existence of the Islamic banking is badly needed within the Indonesian society to become an alternative to the financial conventional institution or system. On the other hand, it must be openly acknowledged that the entitlement of tax, including PPN, which constitutes the source of national income, is truly necessitate, as when the murabahah product is freed from PPN, the income from the tax sector would be decreased. This article attempts to study and review this puzzling problem through legal and juridical approach.